Light conditions during Atlantic salmon embryogenesis affect key neuropeptides in the melanocortin system during transition from endogenous to exogenous feeding - Norland, Sissel; Gomes, Ana S.; Rønnestad, Ivar; Helvik, Jon Vidar; Eilertsen, Mariann (Frontiers in Behavioral Neuroscience, 2023)
During the first feeding period, fish will adapt to exogenous feeding as their endogenous source of nutrients is depleted. This requires the development of a functional physiological system to control active searching for food, appetite, and food intake. The Atlantic salmon (Salmo salar) melanocortin system, a key player in appetite control, includes neuronal circuits expressing neuropeptide y (npya), agouti-related peptide (agrp1), cocaine- and amphetamine-regulated transcript (cart), and proopiomelanocortin (pomca). Little is known about the ontogeny and function of the melanocortin system during early developmental stages. Atlantic salmon (0 – 730 day degrees (dd)) were reared under three different light conditions (DD, continuous darkness; LD, 14:10 Light: Dark; LL, continuous light) before the light was switched to LD and fed twice a day. We examined the effects of different light conditions (DDLD, LDLD, LLLD) on salmon growth, yolk utilization, and periprandial responses of the neuropeptides npya1, npya2, agrp1, cart2a, cart2b, cart4, pomca1, and pomca2. Fish were collected 1 week (alevins, 830 dd, still containing yolk sac) and 3 weeks (fry, 991 dd, yolk sac fully consumed) into the first feeding period and sampled before (1 h) and after (0.5, 1.5, 3, and 6 h) the first meal of the day. Atlantic salmon reared under DDLD, LDLD, and LLLD had similar standard lengths and myotome heights at the onset of first feeding. However, salmon kept under a constant light condition during endogenous feeding (DDLD and LLLD) had less yolk at first feeding. At 830 dd none of the neuropeptides analyzed displayed a periprandial response. But 2 weeks later, and with no yolk remaining, significant periprandial changes were observed for npya1, pomca1, and pomca2, but only in the LDLD fish. This suggests that these key neuropeptides serve an important role in controlling feeding once Atlantic salmon need to rely entirely on active search and ingestion of exogenous food. Moreover, light conditions during early development did not affect the size of salmon at first feeding but did affect the mRNA levels of npya1, pomca1 and pomca2 in the brain indicating that mimicking natural light conditions (LDLD) better stimulates appetite control.